2014
DOI: 10.1016/j.biopsych.2013.10.006
|View full text |Cite
|
Sign up to set email alerts
|

Amygdala Subregional Structure and Intrinsic Functional Connectivity Predicts Individual Differences in Anxiety During Early Childhood

Abstract: Background Early childhood anxiety has been linked to an increased risk for developing mood and anxiety disorders. Little, however, is known about its effect on the brain during early childhood – a period when anxiety-related traits begin to be reliably identifiable. Even less is known about the neurodevelopmental origins of individual differences in childhood anxiety. Methods We combined structural and functional magnetic resonance imaging (fMRI) with neuropsychological assessment of anxiety based on daily … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
200
4
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 231 publications
(226 citation statements)
references
References 63 publications
14
200
4
4
Order By: Relevance
“…Given apparent lateralization effects in amygdalar functionality and subregional connectivity [Aghajani et al 2016, 2016; Baas et al, 2004; Brown et al, 2014; Gabard‐Durnam et al, 2014; Qin et al, 2014; Sergerie et al, 2008; Styliadis et al, 2014], and in line with recent work [Aghajani et al, 2016; Qin et al, 2012, 2014], BLA and CMA region of interest (ROI) masks were created in each hemisphere (see Supporting Information), and used to extract individual participant's mean time series within BLA and CMA complexes. Seed‐based whole‐brain iFC analysis implemented within FSL FEAT [Jenkinson et al, 2012], was then employed to reveal BLA and CMA connectivity patterns [Fox and Raichle, 2007].…”
Section: Methodsmentioning
confidence: 99%
“…Given apparent lateralization effects in amygdalar functionality and subregional connectivity [Aghajani et al 2016, 2016; Baas et al, 2004; Brown et al, 2014; Gabard‐Durnam et al, 2014; Qin et al, 2014; Sergerie et al, 2008; Styliadis et al, 2014], and in line with recent work [Aghajani et al, 2016; Qin et al, 2012, 2014], BLA and CMA region of interest (ROI) masks were created in each hemisphere (see Supporting Information), and used to extract individual participant's mean time series within BLA and CMA complexes. Seed‐based whole‐brain iFC analysis implemented within FSL FEAT [Jenkinson et al, 2012], was then employed to reveal BLA and CMA connectivity patterns [Fox and Raichle, 2007].…”
Section: Methodsmentioning
confidence: 99%
“…However, even within a single disorder, results are conflicting, some reporting hypo-connectivity while others find hyper-connectivity(8;40;48;49). Discrepancy in amygdala-vmPFC connectivity findings may be due to differences in age ranges examined (50;51), not addressing developmental effects (52;53), and the specific amygdala and vmPFC subregions examined.…”
Section: Introductionmentioning
confidence: 99%
“…They found that adults showed greater connectivity between the task-positive network and dorsolateral prefrontal cortex and stronger anti-correlations between the “task negative” network and anterior insula, parietal and posterior cingulate cortices [23]. Chai and colleagues also examined the development of anti-correlated networks in 8-24 year-olds [24] and found that as age increased, anti-correlations also increased between networks (i.e., medial and dorsolateral prefrontal cortex, and between lateral parietal and supramarginal gyrus and precuneus). Authors noted that the correlation between regions in these networks was positive in childhood but negative in adults, with adolescent connectivity levels falling in the middle [24].…”
Section: Typical Developmentmentioning
confidence: 99%
“…Chai and colleagues also examined the development of anti-correlated networks in 8-24 year-olds [24] and found that as age increased, anti-correlations also increased between networks (i.e., medial and dorsolateral prefrontal cortex, and between lateral parietal and supramarginal gyrus and precuneus). Authors noted that the correlation between regions in these networks was positive in childhood but negative in adults, with adolescent connectivity levels falling in the middle [24]. …”
Section: Typical Developmentmentioning
confidence: 99%
See 1 more Smart Citation